2020
DOI: 10.2196/17574
|View full text |Cite
|
Sign up to set email alerts
|

Using Twitter to Surveil the Opioid Epidemic in North Carolina: An Exploratory Study

Abstract: Background Over the last two decades, deaths associated with opioids have escalated in number and geographic spread, impacting more and more individuals, families, and communities. Reflecting on the shifting nature of the opioid overdose crisis, Dasgupta, Beletsky, and Ciccarone offer a triphasic framework to explain that opioid overdose deaths (OODs) shifted from prescription opioids for pain (beginning in 2000), to heroin (2010 to 2015), and then to synthetic opioids (beginning in 2013). Given th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…27 In the context of internet surveillance, Anwar et al sought to determine if opioid-related Twitter posts could have been used to identify the three waves of the opioid crisis in North Carolina from 2009 to 2017. 34 They used a natural language processing (NLP) approach to identify opioid-related tweets. Their findings indicate that the annual number of heroin-and synthetic opioid-related Twitter posts were associated with annual heroin-and synthetic opioid-overdose death rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In the context of internet surveillance, Anwar et al sought to determine if opioid-related Twitter posts could have been used to identify the three waves of the opioid crisis in North Carolina from 2009 to 2017. 34 They used a natural language processing (NLP) approach to identify opioid-related tweets. Their findings indicate that the annual number of heroin-and synthetic opioid-related Twitter posts were associated with annual heroin-and synthetic opioid-overdose death rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Their findings indicate that the annual number of heroin-and synthetic opioid-related Twitter posts were associated with annual heroin-and synthetic opioid-overdose death rates, respectively. 34 Chary et al used NLP (semantic distance specifically) to identify Tweets related to the non-medical use of prescription opioids (NMPO) from 2012 to 2014 and showed these Table I. Papers that met study inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the large number of adolescents who misuse opioids [ 36 ], little is known about how social media influences adolescents’ use or misuse of opiates. One study found an association between a participant tweeting about opioids and offline opioid overdoses [ 39 ]. Furthermore, previous research has shown that engagement with alcohol-related and e-cigarette–related social media is associated with more offline use of these substances [ 40 , 41 ].…”
Section: Studymentioning
confidence: 99%
“…Specifically, we provide a more nuanced understanding of personality's influence on fatal opioid overdose through the five distinct dimensions of the five-factor personality trait model. To do so, we build on a burgeoning stream of health care informatics, which establishes social media posts on the topic of opioid substances as a timely indicator of opioid overdose mortality [24,53], by using a combination of advanced computational techniques (cloud computing and text mining) and robust econometric analysis to expand the scope of user-generated content relevant to infoveillance beyond posts directly mentioning opioids. Our study also has several practical implications for health care providers and administrators, as its findings can be applied in opioid overdose prevention and surveillance based on the local counties' prevalent personality traits.…”
Section: Literature Reviewmentioning
confidence: 99%